Controller Networking for Smart Building / Mohd Shah Rulzafian Zakaria and Sharulnizam Mohd Salleh - Zakaria, Mohd Shah Rulzafian; Mohd Salleh, Sharulnizam (2005)
Controller Networking for Smart Building is a method to communicate two or more microcontroller with a minimum number of system wires. This method called Controller Area Network (CAN). In order the CAN could be used, there is circuit design and programming to be followed This is where the important of PIC microcontroller, CAN controller and CAN driver. The combination of these devices can make the controller networking possible using Serial Peripheral Interface (SPI). By completing this project, we can create new kind of circuit networking with less wire, cost, and more reliable. We also can explore the usage of the PIC microcontroller by learning its programming using the MP LAB software. The purpose of the project is to create more efficient switching system to control the light and fan will be accomplished by completing this project. This can provide more reliable control system for smart building.